Heavy metal content presence in soil and uptake by paddy at Kg Padang Tengah, Merlimau Melaka / Abdul Basit Yusoff - Yusoff, Abdul Basit (Faculty of Plantation and Agrotechnology, 2016)
Heavy metals element which accumulated is well known have a significant effect towards health humans. These study aims to assess the heavy metal content presence in soil and uptake by paddy which are exceed or not exceed the permissible limits in soil and plant parts (grain). Heavy metal may come from natural and human activities which give contamination problem to environment. From visual assessment, the locations did not appear to have been affected by industrial waste. Soils samples were collected from the depth 0-30 cm depth, air dried and ground to pass a 2.00 mm sieve. Heavy metals were extracted from soil samples by Mehlich-l(extraction for macronutrients and micronutrients) and for plant analysis used dry ashing methods and also both of these methods are determined by Inductively Coupled Plasma (lCP). Concentrations of nonessential and essential heavy metals in this experiment such as iron, manganese, copper and chromium are measured in the soil and plant part (grain). The concentrations of heavy metal in paddy field soils not exceed allowable limits and also found higher in the plant parts (grain) exceed the allowable limits.